Current trends in psychotherapies and psychosocial interventions for people with dementia: a scoping review of randomized controlled trials - Vicente, Célia; Fernandes, Sónia; Romão, Ana; Fernandes, Júlio Belo (Frontiers in Psychiatry, 2024)
An outcome of dementia is a progressive decline in cognitive function. Implementing psychotherapies and psychosocial interventions is crucial for bolstering cognitive abilities, promoting independence, and elevating the quality of life for individuals with dementia. This review aims to identify current trends in psychotherapies and psychosocial interventions for people with dementia. A Scoping review was developed based on the framework proposed by Arksey and O'Malley. The literature search was conducted on electronic databases, including Scopus, Cochrane Central Register of Controlled Trials, MEDLINE, CINAHL, Nursing & Allied Health Collection, and MedicLatina. Executed in June 2023, the search focused on articles published in English, Portuguese, and Spanish between 2013 and 2023. Through this search, 1409 articles were initially identified. After selecting and analyzing the reports, sixteen trials were included in this review. Eight distinct categories were identified, covering different strategies. These categories run from computerized game-based cognitive training and reminiscence therapy to compensatory and restorative strategies, memory and attention training, calculation training, dual-task training, counseling, and personalized goal attainment. The findings of this scoping review highlight the diverse landscape of psychotherapies and psychosocial interventions for people with dementia.